Coastal development and risks of flooding in Morocco: The cases of Tahaddart and Saidia coasts. (April 2020) - Aitali, Rajaa; Snoussi, Maria; Kasmi, Siham
Abstract: Coastal areas provide a large array of ecosystems services, contributing to the economic welfare of local communities. However, they are more and more submitted to both human pressures and natural forcing. Climate change creates additional risks and is expected to intensify the loss and degradation of coastal low lying-areas. The aim of this paper is to assess the risk of flooding due to sea-level rise and storm-surges for two Moroccan coasts: Tahaddart, a relatively underdeveloped coast and Saidia which has experienced intense urbanization over the last decade. Their risk assessment was compared to that carried out on the even more developed coast of Tetouan. The main findings of this study are: (i) the high level of risk that threatens these coasts is due to their low elevation and the value of the exposed assets; (ii) there is a positive relationship between the coastal risk and the build-up rate: the more a coastal area is artificialized, the more its risk index is high; and (iii) Coastal risk assessment is a useful tool that can help decision makers and coastal managers in the development of adaptation strategies and management plans to protect coastal ecosystems and make them resilient in the face of climate change. Highlights: The index-based method is a practical method to preliminary assess coastal risks. The coastal risk depends on the elevation and on the value of the exposed assets. The more a coastline is developed, the more it is at risk of flooding. Coastal risk assessment is a useful tool to identify priority areas for adaptation.